Goofballing of Opioid and Methamphetamine: The Science Behind the Deadly Cocktail - Hazani, Hanis Mohammad; Naina Mohamed, Isa; Muzaimi, Mustapha; Mohamed, Wael; Yahaya, Mohamad Fairuz; Teoh, Seong Lin; Pakri Mohamed, Rashidi Mohamed; Mohamad Isa, Mohd Fadzli; Abdulrahman, Sundus Mansoor; Ramadah, Ravi; Kamaluddin, Mohammad Rahim; Kumar, Jaya (Frontiers in Pharmacology, 2022)
Globally, millions of people suffer from various substance use disorders (SUD), including mono- and polydrug use of opioids and methamphetamine. Brain regions such as the cingulate cortex, infralimbic cortex, dorsal striatum, nucleus accumbens, basolateral and central amygdala have been shown to play important roles in addiction-related behavioral changes. Clinical and pre-clinical studies have characterized these brain regions and their corresponding neurochemical changes in numerous phases of drug dependence such as acute drug use, intoxication, craving, withdrawal, and relapse. At present, many studies have reported the individual effects of opioids and methamphetamine. However, little is known about their combined effects. Co-use of these drugs produces effects greater than either drug alone, where one decreases the side effects of the other, and the combination produces a prolonged intoxication period or a more desirable intoxication effect. An increasing number of studies have associated polydrug abuse with poorer treatment outcomes, drug-related deaths, and more severe psychopathologies. To date, the pharmacological treatment efficacy for polydrug abuse is vague, and still at the experimental stage. This present review discusses the human and animal behavioral, neuroanatomical, and neurochemical changes underlying both morphine and methamphetamine dependence separately, as well as its combination. This narrative review also delineates the recent advances in the pharmacotherapy of mono- and poly drug-use of opioids and methamphetamine at clinical and preclinical stages.